Osteological Development of Yellow Rasbora Fish Rasbora lateristriata (Bleeker, 1854) Treated with Mangosteen Garcinia mangostana L. Peel Simplicia - Paramita, Pradnya; Khasanah, Luthfia Uswatun; Retnoaji, Bambang (Bogor Agricultural University, Indonesia, 2025)
Mangosteen peel simplicia (Garcinia mangostana L.) contains potential ingredients used in medicine. A toxicity test of mangosteen peel simplicia is needed before it is used. Wader pari (Rasbora lateristriata) is a potential animal model for toxicity testing. Thus, this study aims to determine the effect of mangosteen peel extract at various concentrations on the behavior and bone structure of R. lateristriata. In this research, fish behavior was observed at 48 hpf (hours post-fertilization) and 30 dpf (days post-fertilization). Bone structure observed at 96 hpf, 7 dpf, 14 dpf, 21 dpf, 28 dpf, 35 dpf, and 42 dpf using the Alizarin Red ‒ Alcian Blue method. Observation data on behavior and bone structure were analyzed descriptively, while the number of vertebrae was analyzed quantitatively using One-Way ANOVA (P < 0.05). The results showed that the ossification of cranium and caudal complex skeleton components in the 1 and 5 μg/mL treatments was significantly behind that of the control and 0.5 μg/mL treatments. Furthermore, 5 μg/mL treatment caused some behavioral and swimming pattern abnormalities in 48 hpf larvae. In conclusion, exposure to 1 and 5 μg/mL mangosteen peel simplicia resulted in skeletal growth inhibition in R. lateristriata. Exposure to 5 μg/mL mangosteen peel simplicia caused abnormalities in the behavior and swimming pattern of 48 hpf larvae.